Importance of healthy eating in the treatment of depression in children (Research, Society and Development, 2021)
Depression is a generic term used to describe a range of depressive disorders such as major depression, dysthymia, bipolar disorder. The aim of the study is to describe the importance of healthy eating in the treatment of depression in children and adolescents. The methodology applied was through bibliographic review, with research survey through databases available electronically in the VHL (Virtual Health Library), Scientific Electronic Library Online (SCIELO), Latin American and Caribbean Literature in Health Sciences (LILACS), consultation in theses, monographs, dissertations, technical manuals and books was also used. The results indicated that healthy eating in a state of depression becomes necessary as it helps to control depressive crises, regulating symptoms and balancing the central nervous system. These results show the need to carry out more work on the importance of nutrition in depression, in order to better understand the process that occurs in the intestine-brain.